Biomarkers of carcinogenicity and their roles in drug discovery and development. Issue 6 (November 2008) - Guan, Ping; Olaharski, Andrew; Fielden, Mark; Roome, Nigel; Dragan, Yvonne; Sina, Joseph
The screening of drug candidates to assess their carcinogenic potential has long been a challenge for drug development. While genotoxic compounds can be readily detected with a battery of standard tests, including short-term in vitro and in vivo assays, predicting nongenotoxic carcinogenicity remains a major challenge. The 2-year rodent bioassay has been held as the gold standard for the assessment of carcinogenic risk to humans. However, due primarily to the continuing doubt over their relevance to human risk assessment, there has been an increased demand for more efficient and accurate approaches to predict and understand human relevant risk of carcinogenicity. Novel biomarkers have helped to shed light on our understanding of the factors that lead to and are characteristic of the carcinogenic phenotypes. Tissue biomarkers of carcinogenicity identified to be concordant with drug exposures resulting in tumor outcome may assist the drug development process by resolving ambiguities, shortening timelines and enabling earlier decisions on compounds. This information could vastly improve the efficiency with which nongenotoxic carcinogens are identified and ensure earlier insight into the relevance for humans.